PENINGKATAN HASIL BELAJAR ILMU MELALUI METODE EKSPERIMENTAL PADA SISWA KELAS IV SDN 1 KERTARAHARJA KECAMATAN PEDES KABUPATEN KARAWANG - Hesti Widiastuti; Yulistina Nur DS; Eri Subekti; Sri Rohartati; Tia Latifatu Sadiah (Postgraduate, University of Mataram, 2024)
The learning outcomes of students' science content are still low. The minimum completeness criteria (KKM) of 70 is not met by most students who take the class IV test. This is because students do not want to participate in learning because learning activities are still dominated by lectures. The purpose of the study was to improve the learning outcomes of science material on changes in the form of objects based on the problem. Data from 27 fourth grade students were collected and presented using an experimental approach. There were two cycles when the research was conducted in the even semester of the 2022/23 academic year. Planning, implementing, observing, and reflecting are part of the research procedure. In terms of pre-cycle learning results, the average benefit of learning outcomes reached 60 or 33%, the first cycle benefited the average learning outcomes reached 72 or 67% of students mastered the learning completely while the second pattern increased. student learning outcomes increased to 83 or 92.5% of students achieved learning authority. Therefore, the material changes in the form of objects in class IV SDN 1 Kertaraharja can be improved by the experimental method.